Culturally responsive parent mentoring model for the early childhood to primary school transition in indonesia: design, validation, and effectiveness - Agustini Agustini; Wenny Hulukati; Abd. Hamid Isa; Pupung Puspa Ardini (Jurnal Konseling dan Pendidikan, 2026)
This study aimed to design and validate a parent mentoring model to strengthen children's foundation ability readiness during the transition from early childhood education (PAUD) to primary school in Gorontalo Province, Indonesia. Employing a Research and Development (R&D) approach guided by the ADDIE framework, the study progressed through analysis, design, development, implementation, and evaluation phases. Mixed-methods data were collected from parents, teachers, and children through expert validation, surveys, interviews, and a one-group pretest-posttest design. Quantitative findings revealed significant improvements in children's socio-emotional regulation (d = 0.85), independence (d = 0.78), and early literacy (d = 0.65) post-intervention. Qualitative results indicated enhanced parental understanding of holistic readiness, improved family-teacher communication, and reduced transition-related stress. Expert validation confirmed high content validity (CVI > 0.80), construct validity, and ecological validity, with implementation fidelity exceeding 85%. The research introduces a co-designed, culturally responsive mentoring model uniquely integrating parental reflection logs, localized stories, and practical activities specifically tailored to the Indonesian PAUD-primary transition context. The validated model offers a scalable, adaptable framework for policymakers and educators to systematically engage parents in supporting children's holistic development during educational transitions. Grounded in socio-cultural and developmental theories emphasizing guided participation, this study demonstrates that structured parental mentoring effectively bridges home-school environments, strengthening early educational continuity.